(untitled) (Journal of Forest and Livelihood, 2024)
The paper, based on observations drawn from Siraha district, highlights some of the complexities involved in the management and use of Terai forests. It is argued that while the Terai forest needs a decentralized management approach, it requires a participatory approach different from the hill model, which tends to focus on people living in the proximity of the forest. The paper argues that it is critical to embrace multitudes a/stakeholders extending up to miles away to the south of the Terai despite the complexities involved in the intervention.